Pemodelan Matematika Risiko Bisnis Kuliner UMKM Kota (Studi Kasus: UMKM Pisang Epe di Pantai Losari) - Muh. Farhan; Naswa Azima Putri; Nurul Khaeria; Atika Fairuq Selviana; Abdul Amanullah; Afiq Naufal; Nur Rezky Ramadhan; Syafruddin Side (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to develop a mathematical model for analyzing business risks in Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Makassar City, specifically among epe banana vendors in the Losari Beach area. MSMEs play a strategic role in the economy, but they are highly vulnerable to risks due to fluctuations in demand, raw material prices, and daily income volatility. Therefore, a quantitative approach is needed to systematically understand these risk dynamics. The method used in this study is a qualitative approach through observation and interviews, combined with mathematical modeling using a SEIR (Susceptible, Exposed, Infected, Recovered) system of differential equations. This model is used to describe the dynamics of MSMEs, which are divided into four compartments: healthy businesses, vulnerable businesses, businesses experiencing losses, and recovering businesses. The analysis results indicate that the system has a stable point of stability, as indicated by negative eigenvalues. Furthermore, the basic reproduction number (R_0 = 0.8889 <1) is obtained, indicating that the risk of business losses is not widely distributed within the system. numerical results also indicate that in the long term, most MSMEs tend to return to a stable or recoverable state. Thus, the developed model realistically depicts the dynamics of MSME business risk and can be used as a basis for formulating risk management strategies to minimize losses and enhance business sustainability.